ASV AeroCat: Small Platform for Teaching and Research in Robotics - S. Neto, Accacio F. Dos; Schettino, Vinícius B.; Lamas, Jennifer M.; Silva, João Marcelo R.; Oliveira, Vitor Eduardo F.; Pires, Anderson G.; Pinto, Milena F. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
Autonomous surface vehicles (ASVs) play a crucial role in various applications such as bathymetric mapping, pollution monitoring, surveillance, and oceanographic studies. However, despite their undeniable importance, there is a scarcity of vessels specifically designed for robotics education. This market gap presents a significant opportunity, as integrating robotics concepts into ASVs could enhance the educational experience, addressing demand in the field of hands-on learning in marine robotics. This paper introduces the ASV AeroCat, a vessel developed with robotics education and research in mind. With reduced dimensions and weight, AeroCat features a differential-aerial propulsion system, making it ideal for operation in shallow water environments. Throughout the paper, details of the design and potential educational applications of the AeroCat will be discussed.